POTENTIAL AND DIVERSITY OF FISH SPECIES IN RIVER WATERS IN DHARMASRAYA REGENCY, WEST SUMATRA PROVINCE - Masrizal Masrizal; Endryeni Endryeni; Lisa Mayasari (Universitas Mataram, 2026)
This study aims to assess the potential and diversity of fish species inhabiting the rivers of Dharmasraya Regency, West Sumatra Province. This study was conducted from May to November 2023 across five rivers: Batang Hari, Batang Momong, Batang Timpeh, Batang Siat, and Batang Jujuhan. Each river comprises two locations, or fishing stations. Fishing is carried out using cast nets, gill nets, scoop nets, and traps. During the study, 2255 fish were caught and classified into five orders, 11 families, 26 genera, and 33 species. Of the 33 species, two species of fish are protected by the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. 106/MENLHK/SETJEN/KUM.1/12/2018, and the Decree of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia No. 1 of 2021, namely Schismatorhynchus heterorhynchus Blkr and Notopterus borneensis (Blkr). The Diversity Index (H`) shows that the diversity of fish species in the river waters in Dharmasraya Regency was relatively high, namely with a diversity index of 3.8973 – 4.5219, there was no dominant species, with a dominance index (D) of 0.0490 – 0.0810, and species richness index (R) of 3.2956 – 4.2892.